2022
DOI: 10.1111/jfr3.12879
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid GIS‐based multi‐criteria decision‐making approach for flood susceptibility analysis in large ungauged watersheds

Abstract: Characterizing and identification of flood-susceptible areas can be a solution to mitigate the damages and fatality rate. This study proposes a novel hybrid MCDM framework to assess flood susceptibility in large ungauged watersheds dealing with data scarcity issues. The proposed method examines the interdependencies and causal relationships between various criteria affecting the flooding procedure using the DEcision-MAking Trial and Evaluation Laboratory (DEMATEL). Moreover, since experts' opinions contain unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…Our research findings reveal significant similarities in the calculated criteria weights between the AHP and BWM methods, with the weights nearly equal. In contrast, studies conducted by Ajrina et al [65], Sahraei et al [66], and Tan et al [67], did not observe such pronounced similarities. Both methods consistently assign notably higher weights to the first three criteria (distance from existing hospitals, distance from main roads, distance from green spaces) and considerably lower weights to the last three criteria (distance from petrol stations, distance from residential areas, and population density).…”
Section: Discussionmentioning
confidence: 76%
“…Our research findings reveal significant similarities in the calculated criteria weights between the AHP and BWM methods, with the weights nearly equal. In contrast, studies conducted by Ajrina et al [65], Sahraei et al [66], and Tan et al [67], did not observe such pronounced similarities. Both methods consistently assign notably higher weights to the first three criteria (distance from existing hospitals, distance from main roads, distance from green spaces) and considerably lower weights to the last three criteria (distance from petrol stations, distance from residential areas, and population density).…”
Section: Discussionmentioning
confidence: 76%
“…■ China is the most prolific country in BWM research, followed by Iran, India, and Turkey. (Wu et al, 2022;Polat et al, 2023), COCOSO (Torkayesh et al, 2021;Ali et al, 2023), MARCOS (Yadav & Kumar, 2023;Ecer et al, 2024), VIKOR (Jain et al, 2023), QFD (Chang et al, 2023), WASPAS (Tavakoli Haji Abadi & Avakh Darestani, 2023), MOORA (Riahi et al, 2023), MULTIMOORA (Koppiahraj et al, 2023), SAW (Darvazeh et al, 2022), TODIM (Kumar et al, 2023), COPRAS (Sahraei et al, 2023), GRA (Hsu et al, 2023), MABAC (Chauhan et al, 2022), DEA (Eskandari et al, 2022), ARAS (Almutairi et al, 2023), and EDAS (Liang et al, 2023), weighting-based MCDM methods, including AHP (Koppiahraj et al, 2023), ANP (Nasiri Khiavi et al, 2023), DEMATEL (Bongo & Seva, 2023), FUCOM (Fazeli & Peng, 2023), and SWARA (Karakuş, 2023), some theories, including game theory (Fard et al, 2022), grey theory (Ulutaş et al, 2022), prospect theory (Zheng et al, 2023), and zero-sum game theory (Li et al, 2021), and mathematical programming, including goal programming (Do et al, 2023), and possibilistic programming (Shaw et al, 2023).…”
Section: The Current Status Of Bwm Researchmentioning
confidence: 99%
“…COPRAS is an algorithm Zavadskas et al (1994) developed for assessing options within a set of mutually exclusive parameters in the multi-criteria space. Sahraei et al (2022) have demonstrated its application in watershed management. The COPRAS model involves the following steps:…”
Section: Coprasmentioning
confidence: 99%